If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4 + 3x) = 136 (4 * 4 + 3x * 4) = 136 (16 + 12x) = 136 Solving 16 + 12x = 136 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 12x = 136 + -16 Combine like terms: 16 + -16 = 0 0 + 12x = 136 + -16 12x = 136 + -16 Combine like terms: 136 + -16 = 120 12x = 120 Divide each side by '12'. x = 10 Simplifying x = 10
| 8x=48 | | 3(x-5)=3+x | | 12y-3=16y-9y | | 2Y+19=23 | | 4x^2-13x+7=8x+2 | | t^2+t=2 | | x^2+4x+p=0 | | 3x-9=1+x | | 6(6+7x)=456 | | 4(-18-2)-5*18=1 | | -2x-1/2=x/5 | | (2x+3)+(x-6)=90 | | 2+2-4+3-7+8= | | -6n+15=-5n-1 | | 2(4-5x)+9=2x-23-8x | | 7(6x+7)=91 | | 5+6x=3+5x-8 | | 3x=2x-17.5 | | 2x/5-2x-1/2=x/5 | | 5*6+5x+6x=30x | | 7(8+x)=98 | | 4(x+3)+28=-4x | | -3x-8=5y+32 | | 6x=4y+8 | | (5x-2)(2x+7)= | | 4(y+3)=3y+13 | | 8(7-x)=4(3x-16) | | 8y-6=6y+6 | | 6(3+2x)=54 | | x^2-13x+15=-3x-1 | | 7x+2=12+x | | -16x-20=-13x+55 |